Development of Flexible Fiber Conditioner in Chemical Mechanical Planarization. (14th October 2019) - Fujita, Takashi; Doi, Toshiro; Arai, Yutaro
Abstract : A flexible fiber pad conditioner, which conforms well to the pad surface, has been developed. Conventional disc-type conditioners have a potential concern of uniform conditioning across the entire pad surface in terms of intermittent contact by face-to-face contact. In the flexible fiber conditioner, each fiber tip functions independently with constant contact force on the pad, by utilizing the bending effect of the flexible fiber. Therefore, the conditioner performs uniform and fine conditioning, following the height variation in the pad surface. Uniform conditioning was verified by a unique method using surface coloration on a pad with height variation. In addition, it was shown that, using the developed conditioner, the chips generated by pad conditioning were very small, and the pad surface was finely scraped and roughened. It was further demonstrated that the developed flexible fiber conditioner shortened the pad break-in process. Moreover, compared with the conventional disk-type conditioner, the developed flexible fiber conditioner resulted in a uniform polishing profile even in the midst of the break-in process. The results indicate that it is important for the break-in of the polishing pad, to uniformly scrape and roughen the entire area of the pad while following the pad surface, rather than planarizing the surface.